Fusion of Emotional Thinking and Mental Health of Students in Vocal Music Teaching - Qi Yang; Chao Yu (Occupational Therapy International)
Vocal psychology belongs to the branch of music psychology, which is the cross-study of vocal art and psychology, and is also a new discipline with both theory and application. Vocal singing uses a thinking, conscious person as an instrument that is necessarily governed by the psyche over the physiology, relying on the brain to direct the movement of the singing muscles and the coordination of the vocal organs. The purpose of this thesis is to explore the application of vocal psychology in vocal singing and teaching, to explain the generation and development of various psychological phenomena in singing activities, to reveal the role and significance of various psychological factors, to provide singers with a theoretical basis for psychological aspects, and to correctly understand the scientific laws of the inner psychology of vocal singing. The effectiveness of classroom teaching is reflected in effective and efficient aspects. The effectiveness of a vocal lesson can be measured by the criteria of whether the teaching is oriented, scientific, artistic, and efficient. Effective teaching design is the basis of teaching effectiveness, elaborate teaching organization is the guarantee of teaching effectiveness, and flexible teaching methods are the root of teaching effectiveness; all three need to be closely combined and organically unified. Effective teaching design is a holistic thinking before the implementation of teaching; all factors related to teaching, practice, and evaluation should be fully considered in the teaching design; teachers should take the learning effect of students and the cultivation of employability as the starting point for effective teaching design; and the classroom teaching of “vocal music” is a “process” and teachers should teach in accordance with the teaching design. They should focus on guiding students to experience and cultivate their abilities in a series of “processes” such as the emotion of vocal music, the teaching situation, the effect of listening, the creation of expression, and the aesthetic value. In addition, teachers should combine the teaching methods of transmission and inspiration, classroom teaching, and after-school training and combine relatively fixed teaching methods with flexible teaching methods to maximize the effectiveness of teaching.